Research methodology of youth interpersonal communication based on modern technology - Krstić Milan; Skorup Ana; Gavrić Gordana (Trendovi u Poslovanju)
The evolution of human communication initiated by direct non-verbal and sign communication, along with the occurrence of language is transformed into verbal communication so that nowadays, with the development of information communication technologies (ICT), the extent of the application of indirect communication is increased, bringing completely new ways of communication. Modern communication based on ICT has changed the way of communication and has brought numerous benefits for participants of the communication process in several aspects of communication (mass availability, development time, speed of communication, possibilities of combining different multimedia forms, ease of communication, etc.), also including some negative effects in various aspects of communication (protection of privacy, simplification of linguistic content, alienation of people, etc.). As the young population uses modern forms of communication the most, it is meaningful to organize systematic research on the subject mentioned. In this regard, this paper presents the projected methodology for researching contemporary interpersonal communication among young people, with the target population selected from college and secondary school students.